KESEHATAN MENTAL MASA KINI DAN PENANGANAN GANGGUANNYA SECARA ISLAMI - Widiya A Radiani (JOURNAL OF ISLAMIC AND LAW STUDIES, 2019)
Abstract Mental disorders if not handled properly, will get worse, and in the end can burden families, communities, and the government. The method used in this paper is to use descriptive exploratory analysis, through literature review and secondary data studies. The results of the study show that the study of the 2018 Riskesdas data revealed that the prevalence of severe mental disorders in the Indonesian population is 7% (per mile of the total population) and most were in Bali, Yogyakarta, NTB and Aceh. The mental emotional disorders with symptoms of depression and anxiety amounted to 9.8% and most were in Central Sulawesi, Gorontalo, NTT and Maluku. The mental health movement must prioritize prevention and the role of the community to help optimize the mental functions of individuals. Mental health is not only related to medical or psychological problems, but also has a socio-cultural dimension to the spiritual and religious dimensions. For this reason, not only medical treatment but also religious handling, such as being patient, getting used to implementing and disciplining commendable habits, doing positive activities, increasing confidence in certain values (truth, beauty, virtue, faith and others), reading prayers, read Al-Quran, remembrance of remembrance and hadith of the Prophet, performing evening prayers, associating with people who are good or pious, fasting, follow Islamic studies, follow recitations of recitation and jurisprudence, follow the Assembly of Remembrance and learning Da'wah and science Islam.  Keywords: Mental Health, Islamic Intervention  Abstrak Gangguan mental jika tidak ditangani dengan tepat, akan bertambah parah, dan pada akhirnya dapat membebani keluarga, masyarakat, serta pemerintah. Metode yang digunakan pada tulisan ini adalah  menggunakan analisis deskriptif eksploratif, melalui tinjauan literatur dan kajian data sekunder. Hasil Penelitian menunjukkan bahwa kajian data Riskesdas 2018 diketahui prevalensi gangguan mental berat pada penduduk Indonesia 7% (per mil dari jumlah penduduk) dan terbanyak terdapat di Bali, Yogyakarta, NTB dan Aceh. Adapun gangguan mental emosional dengan gejala-gejala depresi dan kecemasan sebesar 9,8% dan terbanyak terdapat di Sulawesi tengah, Gorontalo, NTT dan Maluku. Gerakan kesehatan mental harus lebih mengedepankan pada aspek pencegahan dan peran komunitas untuk membantu optimalisasi fungsi mental individu. Kesehatan jiwa tidak hanya terkait masalah medis atau psikologis semata, tetapi juga mempunyai dimensi sosial budaya sampai dimensi spiritual dan religius. Untuk itu diberikan tidak hanya penanganan secara medis tetapi juga perlu penanganan secara keagamaan seperti bersikap sabar, membiasakan diri dalam melaksanakan dan mendisiplinkan kebiasaan terpuji, melakukan kegiatan positif, meningkatkan keyakinan atas nilai-nilai tertentu (kebenaran, keindahan, kebajikan, keimanan dan lainnya), membaca doa-doa, ayat-ayat Alquran, zikir-zikir dan hadis nabi, melakukan shalat malam, bergaul dengan orang yang baik atau salih, puasa, mengikuti pengajian pengobatan islami, mengikuti pengajian Tajwid dan Fiqih, mengikuti Majelis Zikir serta belajar Dakwah dan ilmu keislaman. Kata Kunci: Kesehatan mental, Penangan gangguan kesehatan mental.